Nutrient Management of Vegetable and Agronomic Row Crops Handbook - Kelly T. Morgan (EDIS)
Through the implementation of a series of targeted cultural practices discussed in this production guide, growers should be able to reconcile economic profitability and responsible use of water and fertilizer. Topics include: proper sampling practices and test interpretations; irrigation management methods and automation; use of alternate fertilizer materials to retain nutrients in the soil but allow adequate supply for crop uptake. Use of these BMPs ensures that adequate fertilizer rates may be achieved by combinations of UF/IFAS recommended base rates and supplemental fertilizer applications. This 199-page handbook was edited by Kelly T. Morgan, and published by the UF Department of Soil and Water Science, February 2015.